Heating of hip joint implants in MRI: The combined effect of RF and switched‐gradient fields. Issue 6 (22nd January 2021) - Arduino, Alessandro; Zanovello, Umberto; Hand, Jeff; Zilberti, Luca; Brühl, Rüdiger; Chiampi, Mario; Bottauscio, Oriano
Abstract : Purpose: To investigate how the simultaneous exposure to gradient and RF fields affects the temperature rise in patients with a metallic hip prosthesis during an MRI session. Methods: In silico analysis was performed with an anatomically realistic human model with CoCrMo hip implant in 12 imaging positions. The analysis was performed at 1.5 T and 3 T, considering four clinical sequences: turbo spin‐echo, EPI, gradient‐echo, and true fast imaging sequence with steady precession. The exposure to gradient and RF fields was evaluated separately and superposed, by adopting an ad hoc computational algorithm. Temperature increase within the body, rather than specific absorption rate, was used as a safety metric. Results: With the exception of gradient‐echo, all investigated sequences produced temperature increases higher than 1 K after 360 seconds, at least for one body position. In general, RF‐induced heating dominates the turbo spin‐echo sequence, whereas gradient‐induced heating prevails with EPI; the situation with fast imaging sequence with steady precession is more diversified. The RF effects are enhanced when the implant is within the RF coil, whereas the effects of gradient fields are maximized if the prosthesis is outside the imaging region. Cases for which temperature‐increase thresholds were exceeded were identified, together with the corresponding amount of tissue mass involved and the exposure time needed to reach these limits. Conclusion: The analysis confirms that risky situations may occur when a patient carrying a hip implant undergoes an MRI exam and that, in some cases, the gradient field heating may be significant. In general, exclusion criteria only based on whole‐body specific absorption rate may not be sufficient to ensure patients' safety.